1988
DOI: 10.2307/1942462
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of the Lizard Cnemidophorus Tigris and Life History Consequences of Food‐Acquisition Mode

Abstract: Energy budgets for the wide-foraging "arthropodivorous" lizard Cnemidophorus tigris were constructed for the reproductive season using doubly labeled water measurements of field metabolic rate (FMR). Rates ofbody mass change, clutch sizes, and clutch intervals were also investigated. FMRs ofboth sexes (males, 298 J ·g-1 ·d-1 ; females, 24 7 J · g-1 • d -1 ) were greater in the reproductive season than during the postreproductive season. This was not due to differences in resting metabolism, but, instead, was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(42 citation statements)
references
References 67 publications
2
39
0
1
Order By: Relevance
“…monticola in the field (but see P6rez-Mellado et al 1987, for the postreproductive period), but we have observed increased male activity and movements during the reproductive period (unpublished data). Also iguanid and teiid males maintain high activity levels during the entire breeding season, because re-peated searches of home range establish an encounter rate of males with prospective mates (Rose 1981;McCloskey et al 1987;Anderson and Karasov 1988). Lizards that maintain territories in the field commonly develop hierarchies in captivity (Stamps 1977;Deslippe et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…monticola in the field (but see P6rez-Mellado et al 1987, for the postreproductive period), but we have observed increased male activity and movements during the reproductive period (unpublished data). Also iguanid and teiid males maintain high activity levels during the entire breeding season, because re-peated searches of home range establish an encounter rate of males with prospective mates (Rose 1981;McCloskey et al 1987;Anderson and Karasov 1988). Lizards that maintain territories in the field commonly develop hierarchies in captivity (Stamps 1977;Deslippe et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have focused on variation in energy reserves, growth, and metabolism within populations, especially in the context of the cost of reproduction. For example, metabolic rates measured in the fi eld were higher in reproductive versus nonreproductive females of several species (Nagy 1983, Anderson & Karasov 1988. A number of correlational and experimental studies indicate that a common effect of current reproduction may be the reduction of internal reserves, which impacts future reproduction either by reducing survivorship or by reducing nutrients required for future reproduction (Landwer 1994, Schwarzkopf 1994, Doughty & Shine 1997, 1998, Wilson & Booth 1998.…”
Section: Lizardsmentioning
confidence: 99%
“…In many species, food intake is reduced during the reproduction because animals allocate preferentially their time and energy to different activities such as looking for mates or territorial defense (Doucett et al, n.d;Cherel et al, 1988;Anderson and Karasov, 1988;Barboza and Jorde, 2001;Esteve, 2005). Thus, during reproduction the energetic demand is expected to be high whereas feeding is reduced.…”
Section: Plasma Metabolite Variations During Reproductive Seasonmentioning
confidence: 99%